2008
DOI: 10.20932/barataria.v0i9.178
|View full text |Cite
|
Sign up to set email alerts
|

La perspectiva de género

Abstract: RESUMENEste artículo tiene por objetivo exponer cómo los procesos de pobreza y exclusión social de las mujeres y de los hombres hay que analizarlos desde la perspectiva de género. Perspectiva que permite explicar de qué forma la posición económica de las mujeres viene determinada por la división sexual del trabajo, y se explica gracias a la existencia del orden patriarcal, al sistema de dominación masculina en el que hombres y mujeres son definidos como seres humanos diferentes, cada uno de ellos con sus propi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…In this regard, research works have been found on the line of female entrepreneurship. The problems that have been addressed regarding female entrepreneurship are the constant marginalization, discrimination and segregation of women, analyzed from a gender perspective, since the economic, political and social position of women is regulated by patriarchy where each gender is pigeonholed in their own roles and responsibilities (Moreno S. E, 2018), (Moreno S. E, 2013), (Astoraga, 2019), (Úrsula, 2016), (Brunet Icart, 2008) and (Paredes Hernández, Leal Castillo, & Saavedra García, 2019).…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, research works have been found on the line of female entrepreneurship. The problems that have been addressed regarding female entrepreneurship are the constant marginalization, discrimination and segregation of women, analyzed from a gender perspective, since the economic, political and social position of women is regulated by patriarchy where each gender is pigeonholed in their own roles and responsibilities (Moreno S. E, 2018), (Moreno S. E, 2013), (Astoraga, 2019), (Úrsula, 2016), (Brunet Icart, 2008) and (Paredes Hernández, Leal Castillo, & Saavedra García, 2019).…”
Section: State Of the Artmentioning
confidence: 99%
“…Similarly, gender inequality lies in Latin America, which has three aspects: maternal mortality rate and birth rate in adolescents, the low representation of women in positions of power and finally participation in the labor market, this harms the exercise of human rights, economic efficiency, and demands urgent change (Úrsula, 2016), (Brunet Icart, 2008), (Azpiazu, 2013) and (Camarena Adame & Saavedra García, 2018).…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha evidenciado que algunos de los roles sociales asignados a las mujeres influyen en las tres esferas de su vida: la pública, la privada y la personal. De acuerdo con Brunet (2008), en el ámbito privado intervienen las responsabilidades que se atribuyen a la maternidad, como el cuidado y educación de hijas e hijos, el trabajo doméstico y mantenimiento del hogar, así como el cuidado de la relación de pareja/matrimonio; en su desarrollo en el ámbito público destacan el tipo de ocupación desempeñada en el sector laboral; mientras que en la esfera personal se refiere al tiempo dedicado a sí mismas, como es el de esparcimiento.…”
Section: Palabras Claveunclassified
“…Cabe destacar las actividades invisibles que realizan las mujeres y que corresponden al trabajo no remunerado y no reconocido, como las que atañen al cuidado de la casa y la familia. Adicional a las responsabilidades maternas se suman las actividades de la administración del hogar y la familia, entonces se habla de hasta una triple jornada laboral que no es remunerada (Brunet, 2008), lo que explica las condiciones por las que se presenta el denominado suelo pegajoso.…”
Section: Palabras Claveunclassified